Letter to the editor. Issue 1 (2nd January 2016) - Mooses, Martin; Mooses, Kerli; Haile, Diresibachew W.; Durussel, Jérôme; Kaasik, Priit; Pitsiladis, Yannis P.
Abstract: Santos-Concejero and Tucker argued in their letter to the editor that in our study the running economy in achieving superior performance was overlooked due to some methodological aspects. Having given the remarks of Santos-Concejero and Tucker appropriate consideration, in this letter to the editor, we argue that our paper does not downplay the influence of running economy on the determinants of the East African running phenomenon, but rather adds novel insights into the interaction between running economy, maximal oxygen uptake and performance.